Anticipating Unipolar Depression and Bipolar Depression in young adult with first episode of depression using childhood trauma and personality - Liu, Jiali; Wang, Yuanyuan; Wilson, Amanda; Chen, Hui; Liu, Peiqu; Chen, Xianliang; Tang, Huajia; Luo, Chenyuli; Tian, Yusheng; Wang, Xiaoping; Cao, Xia; Zhou, Jiansong (Frontiers in Public Health, 2023)
Objective Relevant research focusing on young adults with Unipolar Depression (UD) and Bipolar Depression (BD) is limited. The current research aims to investigate childhood trauma and personality traits in young adults with UD and BD. Methods Two hundred and thirty-five patients in a first depressive episode (diagnosed UD and BD), 16–25 years old, were recruited from Second Xiangya Hospital. And 79 healthy controls (HC) were recruited from the community to form the comparison group. Patients' childhood trauma was measured by the Childhood Trauma Questionnaire (CTQ), and personality was measured by Eysenck Personality Inventory (EPI). The Kruskal-Wallis test was used to compare depression, anxiety, CTQ, and EPI scores between the HC (n = 79), UD (n = 131), and BD (n = 104) groups. Factors independently associated with mood disorders and BD were determined using binary logistic regression analyses. Results Compared with HC, mood disorders had more severe anxiety and depression symptoms, and higher CTQ. Emotional abuse (OR = 1.47; 95% CI = 1.08–2.01), emotional neglect (OR = 1.24; 95% CI = 1.05–1.46), and neuroticism (OR = 1.25; 95% CI = 1.16–1.35) were associated with significantly increased odds of mood disorders. Whereas, higher extraversion scores were a protective factor for mood disorders. Compared with UD, BD had more severe anxiety symptoms, and higher CTQ, than extraversion and neuroticism personality scores. Anxiety (OR = 1.06; 95% CI = 1.02–1.08) and extraversion (OR = 1.05; 95% CI = 1.03–1.09) were associated with significantly increased odds of BD. Conclusion Interventions to prevent childhood trauma may improve young adults' mental health. Using childhood trauma and personality to anticipate BD and UD creates more accurate treatment for young adults with first depression.